Effect of sintering pressure on microstructure and mechanical properties of hot-pressed Ti6Al4V-ZrO2 materials. (15th April 2017) - Madeira, S.; Pinto, A.M.P.; Rodrigues, L.C.; Carvalho, O.; Miranda, G.; Reis, R.L.; Caramês, João; Silva, F.S.
Abstract: The development of new design approaches for biomedical applications using conventional and well accepted bio inert materials is an actual challenge. This study proposes a bilayered materials design approach obtained by hot pressing and is concerned with the influence of sintering pressure on the interface reaction between titanium alloy (Ti6Al4V) and zirconia (ZrO2 ), on density and mechanical properties of the Ti6Al4V-ZrO2 . For this purpose, different sintering pressures were studied (P = 5, 20 and 100 MPa). Bilayered materials were produced by hot pressing process, at T = 1175 °C. Microstructural characterization showed that Ti6Al4V reacts with ZrO2 (for P ≥ 20 MPa) and that the interface reaction is strongly dependent on pressure. Additionally, an oxygen-deficient ZrO2 − x black zirconia layer was obtained for specimens produced at P = 20 and 100 MPa as result of decreased O/Zr ratio due to Ti diffusion into ZrO2 side. Young's modulus and hardness properties were evaluated by nanoindentation test. The results showed that these properties are influenced by sintering pressure, increasing with an increase on sintering pressure, with the highest improvement for specimens produced at higher pressure. Graphical abstract: Highlights: This study proposes a bilayered materials design approach obtained by hot pressing for biomedical applications. The effect of sintering pressure on chemical composition and mechanical properties (namely H and E) was studied. Interface reaction and mechanical properties are strongly dependent on sintering pressure. The highest hardness and modulus were found for materials produced at P = 100 MPa. An interesting blackening phenomenon on ZrO2 layer was described and discussed in light of the variation of O/Zr ratio.